(untitled) (Journal of Foreign Language Studies, 2024)
The impersonal phrase, which is a typical linguistic phenomenon and frequently used in the French language, actually causes difficulties for Vietnamese learners. However, in French-language books, the classification and the identification of this type of sentence are inconsistent and vary according to each author. In this study, we will discuss how to identify “impersonal construction” and “impersonal phrase” as well as how to classify the impersonal phrase in French, from which to propose the specific suggestions for Vietnamese learners.